Livelihoods approach: coffee farmer’s strate - gies to deal with pressures in Costa Rica’s rural areas. - Alonso Ubieta, Suyen (2019)
This article aims to identify the main capitals that affect the number of strategies used by families dedicated to coffee production as a sustainable livelihood in Costa Rica. The data was collecting during 2010-2011, through a random sample of 399 coffee producers located in the cantons of León Cortés, Nicoya, Hojancha and Nandayure, Costa Rica. In our methodological approach, we use the factor analysis technique and a negative binomial regression model to explain the relationship between the number of strategies (dependent variable) and family´s capital. The results of the regression explain how human capital (knowledge and skills) and natural and social capital can determinate the number of strategies adopted by families. The limitation of the proposed model is that it omits other variables, such as context (exogenous difficulties), which could be more related to the number of strategies to subsist in the rural environment that is the same loss of capital.